Subjective Voice Handicap and Vocal Tract Discomfort in Patients With Cochlear Implant - Lukaschyk, Julia; Illg, Angelika (Journal of voice, 2025)
Changes in the auditory system, for example due to hearing impairment, can cause changes in breathing, phonation, and articulation. Aim of this study was to provide first data on subjective Voice Handicap and Vocal Tract Discomfort in subjects with hearing impairment and cochlear implant (CI) after initial fitting. Prospective cross-sectional study A total of 111 participants (57 female and 54 male) between 20 and 85 years of age (mean = 58.21, SD = 14.96) were recruited between October 2019 and March 2020 from the Clinic of Otorhinolaryngology at Medical University of Hannover. Participants were tested after initial CI fitting, six weeks after implantation, using the German version of the VTD (Vocal Tract Discomfort) Scale and VHI (9i) (Voice Handicap Index) as well as speech comprehension tests and a specifically developed questionnaire evaluating data concerning voice usage and other influential factors. Statistics included descriptive analysis, group comparisons (t-Test), Pearson correlation coefficient between VTD Scale and VHI, and hearing status. Patients with CI did show low scores in VTD Scale and VHI-9i (VTD mean = 7.85 [SD = 10.4]; VHI-9i mean = 4.04 [SD = 5.77]). We found neither a correlation between any of the speech comprehension tests and the VTD Scale nor the VHI-9i. Further, we could show no correlation between subjective Voice Handicap and/or Vocal Tract Discomfort and age or the kind of treatment. Patients included in this study did not show more subjective Voice Handicap or Vocal Tract Discomfort than normal hearing peers. Scores of VTD Scale and VHI-9i did not depend on the duration of hearing loss, speech comprehension, kind of treatment or age.